Are female students less satisfied with doctoral candidacy experiences? Evidence from 108 countries - Changhong Teng; Chunmei Yang; Guanghao Wu (Humanities & Social Sciences Communications)
Abstract Satisfaction is a crucial indicator of higher education student experience, and lower doctoral student satisfaction may lead to reduced productivity and higher attrition. Considering that empirical research on gender differences in satisfaction remains rather scarce, this study explored the gender differences in satisfaction with doctoral studies as well as the underlying rationales for these differences, utilising data from 6372 doctoral students in 108 countries in the 2019 Nature Global Doctoral Student Survey. The research outcomes show that women have a lower satisfaction rate in pursuing a doctoral degree than men, and the probability of their satisfaction rate decreasing is 3.88% higher. The mechanism analysis reveals that the main factors causing relatively lower satisfaction among female doctoral students are their higher probabilities of encountering gender discrimination and sexual harassment and their greater difficulties in attaining a work-life balance. Moreover, overworked female doctoral students and those from low-income and lower-middle-income countries have relatively lower satisfaction compared to their male counterparts. Our empirical evidence uncovers the intricate challenges that female doctoral students encounter and provides valuable insights for improving the doctoral study environment and promoting gender equality.